Perancangan Pembangkit Listrik Dengan Mengkonversi Motor Induksi Sebagai Generator Induksi Magnet Permanen - Dzikri, Nur Muhammad; , Agus Supardi, S.T., M.T (2016)
Energy permanent magnet is one of the free energy that is being done much research and utilization in the use of various electrical components one needs an induction generator. Induction generator is a very important component for generating electrical energy with a mechanically driven by a prime mover such as water turbines, steam turbines, or an electric motor that generates electricity. This research aims to design a permanent magnet generator induction by utilizing an induction motor. Generator is designed using a rotor in induction motors that have been modified by using 10 pairs of permanent magnet type neodymium with dimensions magnet 20 x 15 mm cylindrical / tube and stator generator is designed to be two poles with the number of turns 325 windings and use a wire email Germany type with the size 0.4 mm. Permanent magnet induction generator able to generate a voltage of 69.5 V to 223.7 V and a frequency of 33.5 Hz to 50.9 Hz with the preliminary rotation speed of 2000 rpm to 3000 rpm in no-load condition, whereas in loaded condition generator is able to supply 8 incandescent lamps 80 watts with a current of 0.27 A at 3000 rpm.